Conception of active food packaging films based on crab chitosan and gelatin enriched with crustacean protein hydrolysates with improved functional and biological properties. (July 2021) - Hajji, Sawssen; Kchaou, Hela; Bkhairia, Intidhar; Ben Slama-Ben Salem, Rabeb; Boufi, Sami; Debeaufort, Frédéric; Nasri, Moncef
Abstract: This study aims to assess the effect of shrimp and crab protein hydrolysates (SPH and CPH) on structure, physicochemical, antioxidant and antimicrobial properties of composite films based on chitosan and fish gelatin. To this end, protein hydrolysates as bioactive additives were incorporated into edible films at different weight ratios 1.5, 3 and 6% (g/100 g polymer). SPH and CPH enriched films were colored and exhibited higher UV-barrier properties compared to the control chitosan-gelatin film. In addition, an improvement in the mechanical properties and thermal degradation temperatures was also observed with PHs incorporation. Furthermore, the hydrophobicity of the composite films was evaluated by determining the contact angle using different solvents (water, ethylene glycol and diiodomethane) during 120 s. With the PHs incorporation, a significant decrease, which was dependent on time and film composition, in the contact angle was found for the composite films. However, an increase in the surface wettability (especially polar component and surface tension) was observed for enriched films. Therefore, PHs addition increases the hydrophilicity of CS-gelatin based films. Interestingly, the composite films, evaluated by several in vitro assays, displayed higher antibacterial and antioxidant potential than control film. Consequently, composite films are promising alternative for active packaging to hinder food oxidation. Graphical abstract: Image 1 Highlights: Development of composite films based on chitosan enriched with protein hydrolysates. Protein hydrolysates incorporation increased surface wettability of composite films. Incorporation of PHs enhanced the UV-barrier property and thermal stability. Enriched films presented antioxidant and antibacterial activities. Composite films enriched with hydrolysates could be used as active food packaging.